Evolution of the galaxy luminosity function from the combo-17 survey - Wolf, C; Meisenheimer, K; Rix, H (2003)
We use a catalogue of 25,000 galaxies with R < 24 taken from the COMBO-17 survey to investigate the galaxy luminosity function (GLF) at redshifts from z = 0.2 to z = 1.2 and binned into SED-types. These galaxies are selected from the COMBO-17 catalogue and cover a total area of 0.78 deg(2), half of the final COMBO-17 sample.